Rainfall variations in south‐eastern Australia part 2: a comparison of documentary, early instrumental and palaeoclimate records, 1788–2008. (28th December 2012) - Gergis, Joëlle; Ashcroft, Linden
ABSTRACT In part 1 of this study, Fenby and Gergis (Fenby C, Gergis J. 2012. A rainfall history of south‐eastern Australia Part 1: comparing evidence from documentary and palaeoclimate records, 1788–1860. International Journal of Climatology) established a documentary chronology of droughts and wet years in south‐eastern Australia (SEA) from first European settlement in 1788 until widespread meteorological observations begin in 1860. We now compare this newly developed documentary record to a five‐station network of historical instrumental rainfall observations from the Sydney region for 1832–1859, and a 45‐station rainfall network from a broader range of SEA locations over the 1860–2008 period. After assessing geographical biases in the documentary and instrumental record due to population settlement, we identify eastern New South Wales (NSW) as the subregion of SEA that is capable of providing a continuous record of wet and dry years back to 1788. Documentary, historical instrumental and modern rainfall observations are then combined to develop an eastern NSW drought and wet year index over the 1788–2008 period. The eastern NSW drought and wet year index is compared to palaeoclimate reconstructions of SEA rainfall and El Niño–Southern Oscillation (ENSO) since 1788. We investigate the relationship between droughts and wet years in eastern NSW and ENSO back to 1788, noting that the coastal NSW rainfall–ENSO relationship is not as pronounced as in inland areas of eastern Australia. While it is clear that ENSO influences rainfall variability in the broader SEA region, the signal recorded in coastal NSW is weak. This is most likely reflecting local orographic rainfall effects and deficiencies in the wet phase of the documentary record. Nonetheless, this study is the first of its kind in the Australasian region to combine documentary, early instrumental and modern meteorological rainfall observations using internationally comparable techniques, a significant advance in historical climatology for the region. The results of this study provide an opportunity for Australia to be included in cross‐regional drought comparisons from the Indo–Pacific regions of the Southern Hemisphere.